Fun Learning Model: Mere Entertainment or an Innovative Solution for Optimizing Children's Intelligence in the Era of Modern Islamic Education? - Adriyansyah, Adriyansyah; Pranata, Jhon Petet; Sirozi, Muhammad (Journal of Educational Sciences, 2025)
Modern Islamic education faces the challenge of globalization, which demands innovation in the learning process to make it more engaging, interactive, and relevant to the times. One approach increasingly developed is fun learning, a learning model designed to be enjoyable while maintaining educational and religious values. This study aims to analyze whether fun learning is merely entertainment or an innovative solution for optimizing children’s intelligence in the era of modern Islamic education. The method used is library research by reviewing books, scientific journals, articles, and relevant educational documents. The results show that fun learning has a positive impact on children’s intellectual, emotional, spiritual, and social intelligence. This approach fosters learning motivation, enhances conceptual understanding, and strengthens students’ religious character through creative and contextual methods. In conclusion, fun learning is not merely entertainment but an innovative learning strategy aligned with Islamic values and effective in optimizing children’s intelligence potential in modern Islamic education.